Penyusunan Regulasi Badan Penyelenggara Jaminan Sosial Kesehatan Atas Penjaminan Skrining Penyakit Kanker Serviks Berbasis Nilai Keadilan Bermartabat - Ingot Netron Sihaloho, Boy; Agung Widi Wandono, Aloysius; Agus Suswantoro, Tri (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Cervical cancer screening is categorized as a public health effort within the minimum service standards and as an individual health effort for participants in the national health insurance program. Cervical cancer screening is regulated under legislation set forth by the Presidential Regulation, the Minister of Health Regulation, and the BPJS Kesehatan Regulation. However, there are challenges regarding the guarantee of cervical cancer screening, which falls under the minimum service standards and individual health efforts. The guarantee for cervical cancer screening requires coordination between the Minister of Health, the Minister of Home Affairs, and BPJS Kesehatan, as stipulated in the regulations concerning the guarantee of cervical cancer screening. If government funding is unavailable or insufficient, BPJS Kesehatan acts as the guarantor for individual health efforts. This provides dignified fairness for participants in accessing health services. This study will analyze and discuss the regulation of cervical cancer screening guarantees within the regulatory framework, and subsequently how the regulation of cervical cancer screening guarantees is managed within BPJS Kesehatan regulations to ensure dignified fairness